The Influence of Communicatian and Emotional Intelligeence on Employee Performance - Andi Surya; Dewi Silvia (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
This study uses a sample of 59 respondents who are the population of employees at the Department of Irrigation and Settlement of Lampung Province as the object of research. The method of data collection was carried out directly by using questionnaires and interviews with employees at the Bandar Lampung City Satellite Health Center. While the analysis used to determine the effect of the variable (X1) communication, (X2) emotional intelligence on the influence variable (Y) namely employee performance is multiple linear regression analysis, with SPSS 18. The results of this study indicate that by using a standard of 0.05 for the test two sides then 2.5% and n = 59 obtained ttable = 2.00324. Meanwhile, t for communication is seen from the data if the output is 2,447 (t > t-table), then the t test for communication has a positive and positive effect on employee performance. Likewise, emotional intelligence testing shows that t count is 4,641 (t > t-table), so the key to emotional motivation is significant for employee compliance at the Waterworks and Settlement Service of Lampung Province. With the F test using a significance level of 0.05 (d = 5%) obtained F table 3.16. Based on the output, if the calculated F data is 17,936, because F arithmetic > F table, it can be said that together there is a significant influence between the independent variables on the dependent variable (employee performance) at the Satellite Health Center in Bandar Lampung City.